HEPATOBILIARY CHANGES AND THEIR CORRECTION WHEN THE DRUG" CORAL ZINC " IS DILUTED IN PATIENTS WITH ACUTE ALOPECIA DEPOSITION - D. I. Ulugxadjaev; A. B. Pakirdinov (Scholars Digest Publishing, 2024)
Migraine alopecia disease is a disease of a polyethiological nature, the causes that cause the disease in its formation are neurogenic, infectious, the presence of migraine infections, changes in blood vessels, functional changes in the central and vegetative nervous system, pituitary, adrenergic and hormonal disorders at the cell level, which in turn cause hair follicles to enter the body of The role of neurotrophic factors in the development of alopecia is large. Neurotrophic factors control the proliferation process of epidermis cells, control the state of apoptosis, the development cycle of hair follicles, as well as the process of melanogenesis. Nervous and emotional arousal are responsible for the development of neurovegetodistonia, which in turn leads to the appearance of deep disorders in the hair follicles in this disease. The disease is often observed to occur after stressful situations. In particular, such a condition is of particular importance in children. To the opinions of the authors of the series, the impact of a stress condition, one of the triggers of the environment in the occurrence of AA disease in children, is from 9.5% to 80% gacha.
Keywords: Malone dialdehyde, cyclic aminosinmonophosphate, cyclic guanosinmonophosphote, ribonuclease, guanosinmonophosphate, Alani aminotransferase.